2002
DOI: 10.1159/000063686
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Treatment Prevents Alterations in Coronary Smooth Muscle Nuclear Ca<sup>2+</sup> Signaling in Diabetic Dyslipidemia

Abstract: Atorvastatin, an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase, alters bulk myoplasmic Ca2+ regulation and inhibits phenotypic modulation and proliferation of vascular smooth muscle in culture. Nuclear Ca2+ (Can) signaling is tightly coupled to transcriptional events and cell growth. Therefore, we hypothesized that in vivo treatment with atorvastatin would attenuate alterations in mitogen-induced Can signaling associated with coronary atherosclerosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 47 publications
10
42
1
Order By: Relevance
“…This study is a significant extension of our previous work (19,20,22,23) and that of Gerrity et al (47) in several regards. First, we have shown in high fat/CH fed diabetic pigs a strong, direct association of LDL and LDL/HDL ratio with coronary atheroma quantified by the clinically used intravascular ultrasound method.…”
Section: Mechanism For Atorvastatin Protection Of Coronary Atherosclesupporting
confidence: 71%
See 3 more Smart Citations
“…This study is a significant extension of our previous work (19,20,22,23) and that of Gerrity et al (47) in several regards. First, we have shown in high fat/CH fed diabetic pigs a strong, direct association of LDL and LDL/HDL ratio with coronary atheroma quantified by the clinically used intravascular ultrasound method.…”
Section: Mechanism For Atorvastatin Protection Of Coronary Atherosclesupporting
confidence: 71%
“…For VLDL, LDL, and by guest, on May 8, 2018 www.jlr.org Downloaded from HDL lipid content, fractions corresponding to these lipoproteins were collected and assayed for CH and TG concentration by standard enzymatic assay. Certain plasma lipid concentrations at 12 weeks for C, HF, DF, and DF ϩ A pigs were reported previously in studies directed at investigating calcium metabolism in coronary smooth muscle cells (20,23,24). Liver lipids were measured by the HPLC method of Homan and Anderson (25) using a 10 cm ϫ 4.6 mm silica gel column (Spherisorb), a SEDEX 55 evaporative light scattering detector (Richard Scientific, Inc.), and 1,2-di-O -hexadecyl-rac-glycerol as the internal standard.…”
Section: Lipid Measuressupporting
confidence: 53%
See 2 more Smart Citations
“…There are reports that ox-LDL increases intracellular free Ca 2 þ concentration ([Ca 2 þ ] i ) in various smooth muscle preparations. 19,20 To date, however, there is no report about ox-LDL effect in corporal smooth muscle preparation. In our study, we showed that LPC increased [Ca 2 þ ] i and Ca 2 þ influx in isolated myocytes, suggesting that the procontractile action of LPC could be endothelium independent.…”
Section: Discussionmentioning
confidence: 99%